Oligomeric iodosylbenzene sulfate: a convenient hypervalent iodine reagent for oxidation of organic sulfides and alkenes - Yusubov M. S. Mekhman Suleiman-Ogly (Suleimanovich); Yusubova R. Ya. Roza Yavidovna; Funk T. V. Tatyana V.; Chi Ki-Whan; Zhdankin V. V. Viktor Vladimirovich (2009, 2009)
Title screen